A pilot study of metabolomic pathways associated with fatigue in patients with colorectal cancer receiving chemotherapy. (February 2022) - Chou, Yun-Jen; Kober, Kord M.; Yeh, Kun-Huei; Cooper, Bruce A.; Kuo, Ching-Hua; Lin, Been-Ren; Kuo, Tien-Chueh; Tseng, Yufeng J.; Miaskowski, Christine; Shun, Shiow-Ching
Abstract: Purpose: The aim of this pilot study was to evaluate for differences in metabolomic profiles between fatigued and non-fatigued patients with colorectal cancer (CRC) during chemotherapy (CTX). Method: Patients were recruited from the department of surgery in a large medical center in Taiwan. In this longitudinal pilot study, the Fatigue Symptom Inventory and fasting blood samples were collected at three assessments (i.e., prior to surgery (T0), three months (T1) and six months (T2) after surgery). Metabolomic profile analysis was used. Multilevel regression and pathway analyses were performed to identify differences in metabolomic profiles between the fatigued and non-fatigued groups. Results: Of the 49 patients, 55.1% (n = 27) were in the fatigue group. All of the 15 metabolites that had statistically significant group × time interactions in the differential metabolite analysis were entered into the pathway analysis. Two pathways were enriched for these metabolites, namely galactose metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis. Conclusions: The results from this pilot study suggest that pathways involved in galactose metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis are associated with cancer-related fatigue (CRF) in patients with CRC during CTX. These findings are consistent with the hypotheses that alterations in energy metabolism and increases in inflammation are associated with the development and maintenance of CRF. Highlights: Galactose metabolism is associated with cancer-related fatigue. Alterations in tryptophan biosynthesis is associated with cancer-related fatigue. Dietary and exercise areas warrant consideration as potential interventions.